1984
DOI: 10.1083/jcb.98.4.1178
|View full text |Cite
|
Sign up to set email alerts
|

Purification, morphometric analysis, and characterization of the glycosomes (microbodies) of the protozoan hemoflagellate Trypanosoma brucei.

Abstract: Trypanosoma brucei glycosomes (microbodies containing nine enzymes involved in glycolysis) have been purified to near homogeneity from bloodstream-form trypomastigotes for the purpose of morphologic and biochemical analysis . Differential centrifugation followed by two isopycnic centrifugations in an isotonic Percoll and in a sucrose gradient, respectively, resulted in 12-to 13-fold purified glycosomes with an overall yield of 31% . These glycosomes appeared to be highly pure and contained <1% mitochondrial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
107
2
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 198 publications
(114 citation statements)
references
References 38 publications
4
107
2
1
Order By: Relevance
“…This predicts that a 27-fold purification of glycosomes could be obtained. These estimations, however, arc in contrast with our earlier experimental results where glycosomes were only purified 11 -12-fold and from which we concluded that they represented 7.8-8.7% of the cell's protein [4]. The latter value is significantly higher than the one we now obtain when using the purification factors for the individual enzymes.…”
Section: Concentration and Organization Of Glycosomal Constituentscontrasting
confidence: 56%
See 4 more Smart Citations
“…This predicts that a 27-fold purification of glycosomes could be obtained. These estimations, however, arc in contrast with our earlier experimental results where glycosomes were only purified 11 -12-fold and from which we concluded that they represented 7.8-8.7% of the cell's protein [4]. The latter value is significantly higher than the one we now obtain when using the purification factors for the individual enzymes.…”
Section: Concentration and Organization Of Glycosomal Constituentscontrasting
confidence: 56%
“…Since the exact amount of Percoll in our glycosome preparations cannot be quantified, we can not yet correct for it. From the observation that glycosomes represent 4.3% of the total cellular volume [4] and constitute 3.7% of the total cellular protein, it can be calculated that the protein concentration inside glycosomes amounts to 150 mg/ml (assuming 175 mg protein/ml for the trypanosome [4]), a value significantly less than our previous estimate (340 mg/ml [4]). From a protein concentration of 150 mg/ml and the density of protein (approximately 1300 mglml), it can be calculated that 11.5% of the volume of glycosomes is filled with protein.…”
Section: Concentration and Organization Of Glycosomal Constituentscontrasting
confidence: 43%
See 3 more Smart Citations